Infrastructure development as a prerequisite for structural change in Africa - Yselle F. Malah Kuete; Simplice Asongu (African Governance and Development Institute (AGDI), 2021)
Structural change is seen by development economics theorists as a driver of sustained and sustainable economic growth. African countries that have understood this prioritize structural change policies in their national development programs in order to reduce poverty and promote employment through commodity-based industrialization. How does infrastructure development contribute to this process? The purpose of this paper is to answer this question by examining empirically whether the state of infrastructure development in Africa stimulates structural change, understood as the development of the manufacturing sector. After outlining the state of infrastructure quality in the region, and discussing some theoretical channels through which this relationship might pass, we estimate fixed effects models from 52 African countries over the period 2003-2018. Results which are robust to controlling for institutional dynamics and the natural resource curse hypothesis suggest that structural change in Africa is optimized with the development of infrastructure, particularly energy and information and communication technologies. Among other policy implications arising from these findings, the establishment of partnership projects with other developed countries in terms of superstructure for enhanced industrialization is recommended.
Keywords: N67; N77; C23; 330; Infrastructure development; structural change; manufacturing sector; Africa